The performance analysis of single and dual axis sun tracking system: a comparative study - Fahad, Hussain Mohammad; Islam, Aporajita; Hasan, Md. Fahim; Fariha, Wasima (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.